Prevalence of depressive symptoms among elderly and its predictors; a cross sectional study in community Felda Bukit Goh, Kuantan, Pahang - Sulaiman, Nur Suriati; Md Aris, Mohd Aznan; Che' Man, Mohamad; Yusof, Muhammad Zubir (2019)
The world’s population is ageing rapidly. Older people are at risk of having mental illnesses particularly depression but it is often misdiagnosed and undertreated. It affects general wellbeing and daily functions of the patients.